BAHAN AJAR BERBASIS REALISTIC MATHEMATICS EDUCATION PADA MATERI OPERASI HITUNG PECAHAN KELAS V SEKOLAH DASAR - Rizky Aulia Sari; Dian Kusmaharti; Via Yustitia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Learning mathematics in elementary schools usually means students only memorize concepts or formulas without seeing directly the problems related to the concepts so that students mathematical concept retention is low. The objectives of this research are (1) to describe the process of developing Realistic Mathematics Education based mathematics teaching materials for fraction calculation operation material for class V elementary schools (2) to determine the feasibility of Realistic Mathematics Educatio based teaching materials for class V elementary schools. This type of research is Research and Development (R & D) with the ADDIE development model but is only limited to three stages including Analysis, Design, Develop. The data collection methods used were questionnaires and unstructured interviews. The data analysis technique used is qualitative to describe product development and descriptive quantitative to determine product feasibility. The results of this development research are (1) the development product in the form of teaching materials based on Realistic Mathematics Education on fraction counting operations. (2) The results of the product feasibility test obtained a very valid category so that the teaching materials were suitable for use in learning.